No way out - Poblocki, Dan (Poblocki, Dan. Shadow House, 2017)
Four of the orphans who were lured to Larkspur House have made it out of the shadow house alive, but Poppy, Dash, Azumi, and Dylan are still on the grounds of the estate and far from safety--and unless they solve the mystery of what it is that the house wants from them they may never escape.